SDS-POLYACRYLAMIDE GEL ELECTROPHORESIS OF EQUID SEMINAL PLASMA PROTEINS - ARANGASAMY, A; BHUREA, S K (The Indian Journal of Animal Reproduction, 2023)
Twelve and eight semen ejaculates were obtained from three Marwari and two Exotic Jack (Martina franc a) stallions, respectively. They were subjected to Plasma separation immediately after collection by centrifugation at 2000 rpm for 20 minutes and stored at -20° C until analysis. In the seminal plasma the total protein concentration was estimated by lowry method and molecular weight was determined by SOS-PAGE analysis. The overall mean values of total protein were recorded as 29.12±2.47 and 34.29±1 .44 mg/ml, respectively, in marwari and exotic stallion. Thirteen total protein bands were observed in the range of 17-95 kDa in the Marwari stallion seminal plasma. Thirteen total protein bands were observed in the range of 17-101 kDa in the exotic Jack seminal plasma. It can be concluded that among the total proteins, eight protein bands are commonly seen in both the stallion .